Islamic Social Reporting, Intellectual Capital, and Corporate Governance Influence on Maqashid Sharia Performance: A Case Study of Sharia Banks in Indonesia and Malaysia (2017-2022) - Astuti, Puji; Raharja, Surya (Jurnal Maksipreneur, 2024)
This research aims to determine the influence of Islamic Social Reporting (ISR), Intellectual Capital (IC), and Corporate Governance (CG) disclosures on the performance of Maqashid Sharia in Sharia Commercial Banks in Indonesia and Malaysia for the 2017-2022 period. This research includes quantitative research obtained from the annual reports of Sharia Commercial Banks in Indonesia and Malaysia which are published on the respective banks' websites. Sampling used a purposive sampling method with criteria determined by researchers so that a sample of 23 banks from 29 Sharia Commercial Banks was obtained in the 2017-2022 observation period. The type of data used is secondary data with the method used is multiple linear regression analysis to determine the direction and influence of the relationship between the dependent and independent variables. Multiple regression analysis was carried out on time series data during the period 2017-2022 in the Islamic banking industry. By using data processing software SPSS version 22. The research results show that partially Islamic Social Reporting has a positive and significant effect on the performance of the Maqashid Sharia Index, while Intellectual Capital and Corporate Governance have a negative and insignificant effect on the performance of the Maqashid Sharia Index.